Fabricação de próteses para articulação: um estudo comparativo entre processos convencionais e manufatura aditiva em liga de titânio - Lozan, Rodrigo (Universidade Federal de São Carlos, 2024)
Engineering seeks to align itself with medicine, seeking solutions to make the life of the human being increasingly comfortable, and joint prostheses that are implanted directly into the human body are an example of this partnership. So, the aim of this research is to conduct a comparative analysis between two primary manufacturing processes employed in the fabrication of joint prostheses, where analysis focuses on evaluation of surface finish roughness and mechanical properties are performed. The product chosen for analysis was a radial head prosthesis, applied in surgeries called partial elbow arthroplasty. To achieve this objective, specimens made of Ti6Al4V alloy were manufactured using both conventional machining and additive manufacturing techniques, specifically Electron Beam Melting (EBM). Following laboratory tests, tensile tests, three-point flexural tests, surface hardness measurements, and surface finish roughness verification were performed to evaluate the mechanical characteristics. The test’ results showed that both manufacturing processes yield comparable mechanical characteristics, suggesting that more specific requirements should serve as the primary parameter for selecting between them. Thus, the advantages of the additive manufacturing process over conventional machining include: reduction of removed material during the production, and places where a high level of precision is not required, additively manufactured parts can be removed near net shape. The disadvantages are: high fabrication time, high process cost and poor quality of finishing.
Manufacturing processes for joint prostheses. a comparative study between machining and additive manufacturing in titanium alloy
Keywords: Biomaterial; EBM; Propriedades mecânicas; Ensaio de tração; CIENCIAS DA SAUDE::MEDICINA::CIRURGIA::CIRURGIA ORTOPEDICA; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::BIOMATERIAIS E MATERIAIS BIOCOMPATIVEIS; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA::TECNOLOGIA DE PROTESES; ENGENHARIAS::ENGENHARIA BIOMEDICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA MECANICA; ENGENHARIAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::EQUACAO DE ESTADO, EQUILIBRIO DE FASES E TRANSICOES DE FASE; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::EXTRACAO E TRANSFORMACAO DE MATERIAIS; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS::ANALISE DE TENSOES; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS::DINAMICA DOS CORPOS RIGIDOS, ELASTICOS E PLASTICOS; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS::MECANICA DOS CORPOS SOLIDOS, ELASTICOS E PLASTICOS; CIENCIAS DA SAUDE::MEDICINA::CIRURGIA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::CONFORMACAO MECANICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::METALURGIA DE PO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::TRATAMENTO TERMICOS, MECANICOS E QUIMICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::USINAGEM; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::ESTRUTURA DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::PROPRIEDADES FISICAS DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::PROPRIEDADES MECANICAS DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::TRANSFORMACAO DE FASES; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO::MAQUINAS DE USINAGEM E CONFORMACAO; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO::PROCESSOS DE FABRICACAO, SELECAO ECONOMICA